Substitusi tepung ikan dengan Maggot (Hermetia illucens) terhadap pertumbuhan dan efisiensi ikan Nila (Oreochromis niloticus) - Ireyne G. Alorang; Jeffrie F. Mokolensang; Juliaan Ch. Watung; Henky J. Sinjal; Revol D Monijung; Joppy D. Mudeng (e-Journal BUDIDAYA PERAIRAN, 2023)
The purpose s of this research were to determine the effect of fish meal substitution withmaggot with different compositions on absolute, relative, and daily growth of tilapia fry,determine the effect of fish meal substitution with different maggot compositions on theefficiency and FCR of tilapia seeds. This study used a completely randomized design with 5treatments and 3 replications to obtain 15 experimental units. The results showed that fish mealsubstitution had a significant effect on fish growth, feed efficiency and FCR. Feed with theaddition of 40 grams of maggot, namely treatment A, gave good growth results compared totreatments B, C, D, and E. The proximate test results for each treatment found that feed treatmentA, namely the addition of 40 g maggot, showed better protein content compared to treatments B,C, D, and E. For absolute growth, the best results were shown in treatment A of 3.49 grams,relative growth of 112.58%, daily growth of 2.51%, feed efficiency value of 77.79%, andconversion ratio feed of 1.28. Keywords: Aquaculture, growth feed, protein sources, food conversion ratio